ANALISIS PENANGANAN KELUHAN TERHADAP LOYALITAS NASABAH PADA PT. BPRS SEPROVINSI LAMPUNG - Ditta Nur Hidayanti Hidayanti (Islamic Economics Journal, 2020)
The purpose of this research is to find and analyze the handling of complaints against customer loyalty at PT. BPRS in the Province of Lampung. This research is a quantitative study with a questionnaire data collection tool that is distributed to customers of PT. SRBs in the Province of Lampung. The sample used in this study was 100 customers, with a purposive sampling data collection technique.Analysis of the data used in this study is a simple linear regression data analysis. The results found that the handling of complaints can affect customer loyalty of PT. SRBs in the Province of Lampung. The magnitude of the effect of handling complaints on loyalty is 49.3%. Therefore, to maintain customer loyalty PT. BPRS in Lampung Province can make various options such as improving service quality,increasing satisfaction, perceived value, E-Servqual and using mobile banking.